FACTORS, PREDETERMINING STUDENTS’ INTENTIONS TO PROCEED GRADUATE LEVEL STUDIES - Novelskaitė, Aurelija (Acta Paedagogica Vilnensia, 2008)
The main aim of this paper is twofold: to examine students’ intentions to proceed their studies of physics, informatics or mechanics on graduate level and to explore what factors predetermine the intentions, and to discuss their significance in methodological terms. Descriptive statistical analysis demonstrates, that, in general, there are almost equal proportions of students, who intend to strive for master degree and who reject that possibility. However, a more detailed review of the data reveals, that the intentions to proceed studies of informatics, physics, or mechanics are more frequent among male than female students, the intentions vary by field of science, and the intentions differently change in women’s and men’s populations. Series of linear regressions let reveal different structures of factors which predetermine female and male students’ intentions to proceed with their studies in analysed fields of science. Despite the structures rather poor in terms of included factors, they clearly denote that the factors differ depending on students’ gender. Finally, the analysis of reliability of the data collection instrument presents rather warning results: most of scales used were not statistically reliable. However, as it was demonstrated, the reliability depends on respondents’ gender. Concluding, results of the analysis confirm and expand findings of earlier studines in the field. That is, in general, the findings reveal the existence of specific (gender directed, science motivation developing) processes at Lithuanian higher school. Despite there are some methodology related limitations (sample, data collection procedure, and data collection instrument itself), in general, the study presents valuable information about poorly investigated phenomena in Lithuania and suggests some insights for social engineering in the field.